How Cybersecurity Leadership Became the New Critical Managerial Competency in Healthcare Administration - Ebone McCoy (Health Economics and Management Review, 2025)
The healthcare and public health sector is a critical component of national infrastructure responsible for clinical service delivery and safeguarding public welfare during crises. However, its increasing digitalization has exposed it to unprecedented cybersecurity threats. This article examines the multifaceted vulnerabilities of U.S. healthcare systems, including fragmented governance, supply chain fragility, and exploitation of protected health information. Key structural weaknesses identified include outdated cybersecurity protocols, insufficient logistical coordination, and a lack of integrated systems thinking in strategic planning. The COVID-19 pandemic highlighted these deficiencies as hospitals struggled with shortages of equipment, ventilator scarcities, and delayed diagnostics due to broken information-sharing pipelines and poorly secured digital assets. The sector's vulnerability to misinformation and disinformation campaigns further complicates crisis management efforts. The article proposes a roadmap for fostering resilience across healthcare supply chains and digital networks. This includes deploying defense-in-depth architectures, Zero Trust security models, adaptive supply chain strategies, and robust cybersecurity education programs. The integration of artificial intelligence, predictive analytics, and just-in-time inventory systems is explored as essential components of a more agile and threat-resilient healthcare ecosystem. Ethical implications of increased digitalization in healthcare are addressed, including patient privacy concerns, data ownership issues, and potential algorithmic bias in AI-driven solutions. The study emphasizes the need for a balanced approach that leverages technological advancements while maintaining the human-centric nature of healthcare delivery. The role of public-private partnerships in strengthening the sector's cybersecurity posture is examined, highlighting successful collaborative models and proposing frameworks for enhanced cooperation between government agencies, healthcare providers, and technology companies. The article asserts that cybersecurity must be embedded as a core strategic imperative, on par with patient safety and clinical excellence, for the healthcare sector to navigate future crises and preserve institutional integrity. It concludes by outlining policy recommendations and best practices for healthcare organizations to enhance their cyber resilience and overall preparedness for future challenges.